1992
DOI: 10.1007/bf00156998
|View full text |Cite
|
Sign up to set email alerts
|

Mersilene (Polyester), a new suture for penetrating keratoplasty

Abstract: Mersilene (polyester monofilament) seems to be suitable for penetrating keratoplasty because it is strong, shows no degradation by ultraviolet light, is insoluble, so that it can be left in situ, and offers the possibility of regulating postoperative astigmatism by suture adjustment. In 12 patients penetrating keratoplasty was performed with the combined interrupted/running suturing technique, using eight interrupted nylon 10-0 sutures and one running Mersilene 11-0 suture. The results were compared with those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
(17 reference statements)
0
3
0
1
Order By: Relevance
“…Several studies conclude that Mersilene can be used effectively in corneal transplantation, 21Y26 although these studies are noncomparative, evaluating the use of Mersilene sutures alone or in combination with nylon sutures. A study by Ramselaar et al, 26 comparing interrupted nylon sutures combined with either a running Mersilene suture or a running nylon suture, concluded that Mersilene seemed to be suitable for penetrating keratoplasty. In contrast to the aforementioned studies, Bertram et al, 20 concluded that Mersilene was inappropriate for use in penetrating keratoplasty because of its high incidence of complications.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies conclude that Mersilene can be used effectively in corneal transplantation, 21Y26 although these studies are noncomparative, evaluating the use of Mersilene sutures alone or in combination with nylon sutures. A study by Ramselaar et al, 26 comparing interrupted nylon sutures combined with either a running Mersilene suture or a running nylon suture, concluded that Mersilene seemed to be suitable for penetrating keratoplasty. In contrast to the aforementioned studies, Bertram et al, 20 concluded that Mersilene was inappropriate for use in penetrating keratoplasty because of its high incidence of complications.…”
Section: Discussionmentioning
confidence: 97%
“…The smallest available dimensions of nylon and prolene cause a very low tissue reaction and are well tolerated in iris surgery [38]. In a study [110] Mersilene (polyester monofilament) was found to be suitable for penetrating keratoplasty for its strength, no degradation by ultraviolet light, insoluble so that it can be left in situ, and the possibility of suture adjustment for regulation of postoperative astigmatism. In regard to corneal replacement, it is worth mentioning that suturing may result irregular corneal shape, which further affects the visual recovery.…”
Section: Methodsmentioning
confidence: 99%
“…Polyester ve polypropylene sütürün ikiside kalıcıdır, yüksek kopma mukavemetine sahiptir ve nylona benzer şekilde doku reaksiyonu oldukça azdır. 20,21,32 Polybutester: Yeni sütür materyallerindendir. Polyglycol terephthate (%16) and polybutylene terephthate (%84) kopolimerinden oluşan monofilament bir sütürdür.…”
Section: İğne Karakteristikleri Ve Seçimiunclassified